Teaching practices, initial teacher education and remote teaching during the COVID-19 emergency - Vargas-Loáiciga, Carlos (2022)
The arrival of COVID-19 during 2020, led to a series of measures, specially the suspension of face-to-face activities (social, work, educational, among others) to be carried out remotely. Given this, Colypro was interested in diagnosing the teaching situation during the execution of these measures through a national consultation from digital forms. The participating teachers described a series of particular characteristics in which it is concluded that there was not adequate preparation in their professional training for developing teaching practices in non-contact modalities. Therefore, it is necessary to review the initial teacher education processes, as well as to strengthen the continuous training processes by the various institutions involved.